Nutritional, functional, and allergenic properties of silkworm pupae. Issue 8 (29th June 2021) - Wu, Xuli; He, Kan; Velickovic, Tanja Cirkovic; Liu, Zhigang
Abstract: Edible insects are a food source that has high nutritional value. Domestic silkworm pupae are an important by‐product of sericulture and have a long history as food and feed ingredients in East Asia. Silkworm pupae are a good source of protein, lipids, minerals, and vitamins and are considered a good source of nutrients for humans. Silkworm pupae are a valuable insect source of substances used in healthcare products, medicines, food additives, and animal feed. Because silkworm pupae are being increasingly used in the human diet, potential allergic reactions to the substances they contain must be elucidated. Here, we present an overview of the benefits of silkworm pupae. First, we describe their nutritional value. Second, we report their functional properties and applications, focusing on their potential use in the food and pharmaceutical industries. Finally, we consider the current state of research regarding silkworm pupae‐induced allergies. Abstract : Silkworm pupae have high nutritional value and varied biological activities. Silkworm pupae are a valuable insect source for healthcare products, medicine, food additives, and feed. Allergic reactions induced by silkworm pupae need attention and further research.